Effects of Storage Structure Type and Pesticide Type on The Physico-Chemical Properties of Cowpea (Vigna Unguiculatus) After Three Months’ Storage: The Case of Daffiama Bussie Issa District - Berchie, Kwadwo Asante; Maaledoma, Prosper (South Asian Journal of Social Sciences and Humanities, 2021)
Cowpea is an important grain legume widely used as food in Ghana and the world at large. It is a significant protein source used by many people in several countries. However, its postharvest management, especially storage, can be problematic because it is easily attached by storage pest insects, particularly Callosobruchus maculatus. Cowpea storage is crucial as the product is protected against damage and deterioration. Also, it is preserved until such a time that market prices are reasonable before they are marketed, enhancing food security. Cowpea grains that are predisposed to insects often attack significantly reduce the quantity and quality, which renders the product unwholesome for human consumption. A survey will be conducted in Daffiama Bussie Issa District in the Upper West Region of Ghana to identify storage structures and storage protectants used by stakeholders to store cowpea. The cowpea variety to be used for the experiment is called 'songotra' and is considered the people's choice. At the end of the storage period, the physical and chemical properties of the cowpea grains were assessed to confirm whether there is a significant effect on them. Test on the viability of seeds will be conducted. The findings will show which storage structure and protectants proved to be more effective by killing the cowpea weevil and unearth the treatment that will offer the highest and lowest protection. Pairwise Statistical Package for Social Scientists (SPSS) Version 9.0 was used to analyse the survey data. It is recommended that further research is conducted on the quantity of cowpea used for storage with an extended storage period. Effects
Keywords: Effects; Pesticide Physico-chemical; Cowpea; treatment